Warship - Naval Submarines 9 (The Royal Institution of Naval Architects (RINA), 2008)
Founded in 1860, The Royal Institution of Naval Architects is an internationally renowned professional institution whose members are involved at all levels in the design, construction, repair and operation of ships, boats and marine structures. Members of the RINA are widely represented in industry, universities and colleges, and maritime organisations in over 100 countries. RINA enjoys an outstanding reputation for the quality and range of its technical publications and organises an extensive and successful programme of international conferences, seminars and training courses covering a broad range of experience and opinion on research, development and operation of all aspects of naval architecture and maritime technology. For further information please visit www.rina.org.uk